Morphological features of mucous secretory organ and mucous secretion of loach Misgurnus anguillicaudatus skin for friction drag reduction. Issue 1 (20th November 2019) - Seo, Eunseok; Yoon, Gun‐Young; Kim, Hae‐Nyeok; Lim, Jae H.; Kim, Seonghan; Kim, Bumju; Kim, Ki H.; Lee, Sang J.
Abstract: We examined the functional morphology of loach Misgurnus anguillicaudatus skin by using synchrotron X‐ray micro‐computed tomography (SR‐μCT) and high‐contrast staining using osmium tetroxide or phosphotungstic acid (PTA), which enhances the image contrast of soft tissues. The captured high‐spatial resolution images revealed that the surface ornamentations were stuck in the basement membrane of the loach scales. The ornamentations consisting of grooves (radii) and ridges (circuli) that can move freely and bend flexibly. The cross‐sectional lateral microstructures of flat, concave and convex loach skins were observed from a live image of loach skin obtained through dark‐field optical coherence tomography (OCT) imaging. The thickness of loach skin was changed with varying empty space between the mucous‐cell layer and the scales by bending motion of loach. In addition, through direct measurement of drag reduction of loach skin, the mucous layer was found to have a strong influence on the reduction of skin friction. The present results enhance the understanding of the functional morphologies of mucous layer of loach to secrete mucus for skin friction reduction.